2008
DOI: 10.1159/000146242
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Estrogen and Progesterone on Kisspeptin-10-Stimulated Luteinizing Hormone and Growth Hormone in Ovariectomized Cows

Abstract: Background/Aims: Growth hormone (GH) is necessary for optimal reproductive efficiency and its secretion is influenced by sex steroids. This study was designed to determine whether kisspeptin-10 (Kp10) could stimulate GH and if gonadal steroids enhance the GH response to Kp10 in cows. Methods and Results: Intravenous injection of Kp10 at 100 or 200 pmol/kg body weight with or without treatment with estradiol cypionate and/or progesterone increased luteinizing hormone (p < 0.01) plasma concentrations. Plasma con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
55
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 28 publications
7
55
1
9
Order By: Relevance
“…Kisspeptin neurons are found in the hypothalamus [7][8][9], and kisspeptins strongly stimulate the secretion of gonadotropin through a G protein-coupled receptor known as GPR54 [3][4][5]. The actions of these peptides are thought to involve mainly stimulating GnRH's neuronal activity through GPR54 [3][4][5].An administration of kisspeptin, either centrally or peripherally, has been shown to elicit the release of gonadotropins in ruminants [10][11][12][13][14][15] as well as in rats [16,17], pigs [18], monkeys [19] and humans [20,21]. However, in cattle, only two in vivo studies have been conducted [13,14], and the precise effects of kisspeptin on the secretion of pituitary hormones under physiological conditions are unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Kisspeptin neurons are found in the hypothalamus [7][8][9], and kisspeptins strongly stimulate the secretion of gonadotropin through a G protein-coupled receptor known as GPR54 [3][4][5]. The actions of these peptides are thought to involve mainly stimulating GnRH's neuronal activity through GPR54 [3][4][5].An administration of kisspeptin, either centrally or peripherally, has been shown to elicit the release of gonadotropins in ruminants [10][11][12][13][14][15] as well as in rats [16,17], pigs [18], monkeys [19] and humans [20,21]. However, in cattle, only two in vivo studies have been conducted [13,14], and the precise effects of kisspeptin on the secretion of pituitary hormones under physiological conditions are unknown.…”
mentioning
confidence: 99%
“…However, in cattle, only two in vivo studies have been conducted [13,14], and the precise effects of kisspeptin on the secretion of pituitary hormones under physiological conditions are unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the only known humoral action of Kisspeptin was on the HPG axis. However, evidence from cows [19,38,39] and rats [24] is emerging of a stimulatory action on pituitary growthhormone release. In addition to the pituitary, hypothalamus and placenta, GPR54 is expressed in other regions of the brain, as well as the spleen, liver, pancreas and gonads [1,2].…”
Section: How Safe Is Exogenous Kisspeptin Likely To Be?mentioning
confidence: 99%
“…63: [221][222][223][224][225][226] 2017) K isspeptin is mainly produced in the hypothalamus and is biologically active at various lengths of 10 to 54 amino acids. Kisspeptin-54 or kisspeptin-10, either the full length or the C-terminal amidated 10-amino-acid sequence of kisspeptin, potently stimulates luteinizing hormone (LH) secretion in both male and female mammals [1][2][3][4][5][6][7]. Our previous study showed that the stimulatory action of kisspeptin-10 on LH secretion is attributable to the stimulation of gonadotropin-releasing hormone (GnRH) neurosecretion into the hypophyseal portal circulation in castrated goats [8].…”
mentioning
confidence: 99%